Synthesis and characteristic analysis of an inorganic composite phase change materials for medium-temperature thermal storage - B., Devaraj Naik; C., Ramanjaneyulu; V., Santhosh Reddy; R., Sundara Ramam; G., Suresh Babu; T., Vinoth [UNESP]; K., Ravi Kumar; A., Saikiran (Elsevier, 2024)
Composite phase change materials (CPCM) synthesized using inorganic salt (Na2HPO4·12H2O), lime fruit peel biochar (activated), and boron nitride have been explored as a solution for the medium-temperature thermal energy storage systems in this work. The activated biochar and BN concentrations were varied, and the effects of the activated biochar and BN on the thermal properties, chemical, and thermal stability of the phase change materials (PCM) were studied. XRD and FTIR studies confirmed the chemical stability of the synthesized CPCM samples. Leak test results revealed that the addition of biochar and BN has improved the shape stability. TGA studies revealed the superior thermal stability of the CPCM samples. Composite PCM with 2 g of activated biochar and 0.5 g of BN has exhibited better thermal properties with a latent heat of 121.33 J/g, encapsulation efficiency of 55.9%, and thermal energy storage capacity of 98.2% compared to the pure PCM.
Keywords: Composite PCM; Inorganic PCM; Lime fruit biochar; Na2HPO4.12H2O; Pyrolysis